2010
DOI: 10.1016/j.critrevonc.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive geriatric assessment can predict complications in elderly patients after elective surgery for colorectal cancer: A prospective observational cohort study

Abstract: CGA can identify frail patients who have a significantly increased risk of severe complications after elective surgery for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
308
5
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 408 publications
(342 citation statements)
references
References 68 publications
14
308
5
5
Order By: Relevance
“…A systematic review published in 2014 showed that frailty was associated with a nearly 5-fold increase in the risk of serious cardiac and cerebrovascular events (odds ratio 4.89), and this association was stronger in older patients undergoing transcatheter aortic valve replacement (TAVR) (odds ratio 3.31 to 4.89) compared to younger patients scheduled for bypass grafting or valve surgery (odds ratio 1.10 to 3.16) [8]. Of note, however, our findings are in agreement with data indicating discordance between chronological age and individual physiologic reserves [1,4]. This indicates that although age is a risk factor for mortality and postoperative complications, it is not a direct determinant of outcomes among the elderly but rather a correlate of comorbidities [14].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A systematic review published in 2014 showed that frailty was associated with a nearly 5-fold increase in the risk of serious cardiac and cerebrovascular events (odds ratio 4.89), and this association was stronger in older patients undergoing transcatheter aortic valve replacement (TAVR) (odds ratio 3.31 to 4.89) compared to younger patients scheduled for bypass grafting or valve surgery (odds ratio 1.10 to 3.16) [8]. Of note, however, our findings are in agreement with data indicating discordance between chronological age and individual physiologic reserves [1,4]. This indicates that although age is a risk factor for mortality and postoperative complications, it is not a direct determinant of outcomes among the elderly but rather a correlate of comorbidities [14].…”
Section: Discussionsupporting
confidence: 58%
“…These persons are at a much increased risk of trauma (mostly due to falls), disability, and dependence, with a need for long-term care at home or in nursing care facilities [2]. Frailty often coexists with comorbidities (often expressed as the number of concomitant conditions) but these are not synonymous terms [4]. Quality of life of frail subjects is not satisfactory [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies were observational (23 of 35) with a total of 1 153 684 patients available for the analysis. Cohorts were composed of patients undergoing lower gastrointestinal (GI) surgery (10 studies), upper GI surgery (6), mixed GI surgery (4), gynaecological surgery (6), urological surgery (4) and mixed abdominal surgery (6) ( Table  1)1 12, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify frailty, these studies sum the number of frailty characteristics (some of which are geriatric syndromes) present in an older adult prior to an operation. In these studies, the geriatric syndromes of impaired cognition, [7][8][14][15][16] , poor mobility, [7][8][16][17][18] incontinence, 14 functional decline 7-8, 14-15 and having fallen [7][8] are abnormal characteristics used in sum to define frailty which has been closely related to adverse postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%